Comentario “A propósito del artículo la prevención cuaternaria en la atención médica ambulatoria y hospitalaria” - Barcos Pina, Indira; Rodríguez Hernández, Odell; León De la Torre, Alina (Mediciego, 2020)
Two pertinent articles on quaternary prevention have recently been published in the MediCiego magazine: in volume 25, Number 1, the editorial Quaternary prevention in ambulatory and hospital medical care(1) and in the same volume, but in number 3, the letter To the editor About the article quaternary prevention in ambulatory and hospital medical care